Symmetry-dependent spin transport properties of a single phenalenyl or pyrene molecular device. (October 2017) - Fan, Zhi-Qiang; Sun, Wei-Yu; Zhang, Zhen-Hua; Deng, Xiao-Qing; Tang, Gui-Ping; Xie, Hai-Qing
Abstract: Spintronic systems exploit the fact that the electron current is composed of spin-up and spin-down carriers, which are more easily disturbed than electronic systems. Here, we investigate the spin transport properties of a single phenalenyl or pyrene molecule connected to zigzag graphene nanoribbon electrodes by using the non-equilibrium Green's function formalism with density functional theory. We found the difference of the symmetry on these two molecules will bring a remarkable effect on the spin transport properties of the devices. The spin-resolved currents of the single pyrene molecular device are much lower than that of the single phenalenyl molecular device when they all connected to electrodes symmetrically. In addition, we found the change of the connected site will decrease the spin-resolved currents of the phenalenyl-based molecular device drastically, but had no longer any influence with the pyrene-based molecular device. The results will be helpful for us to further understand the transfer of the spin-carriers in the spintronic systems. Graphical abstract: